Tourism and social media: new ways to approach the subject and space in pandemic times - de Almeida Paula, Karine; de Almeida Faria , Teresa Cristina (Geografares, 2021)
The article aims to discuss the interface between tourism, forms of leisure, and social media, especially in times of pandemic due to the rapid spread of Covid-19. Amid the adversities placed in the current scenario, technology has emerged, in a more visible way, as a tool for accessing and sharing information. For this analysis, an exploratory descriptive approach was used, analyzing examples of actions and projects broadcast on the social media of tourist and cultural pages. From the analyzes and interpretations, it was possible to observe several projects and ideas being built to bring tourists closer to space and as a way of spreading tourist and cultural attractions amidst the adversities posed by social detachment. Technology has become a tool in this process, transforming access and sharing of experiences. Social media has acquired an important role in this scenario, providing experiences of visiting tourist places without a predefined physical contact and presenting itself as a complement to tourist experiences.
Keywords: social media; tourist activities; Covid-19